Scalable watermarking for identifying large numbers of viewers - Zolba, Deivis (Lietuvos matematikos rinkinys, 2025)
The study aims to introduce a scalable watermarking model that could be used to design a fast watermarking tool that is invisible and robust enough to identify the content source–viewer. This tool would enable adequate digital copyright protection at scale. To this end, a survey of watermarking methods that could embed unique viewer information in real-time has been carried out. The model can reliably scale frequency-domain watermarking techniques for mass application.